Bridging the 2-Degree Gap with NDCs 3.0: West Africa’s Climate Commitment and Lessons from the First Global Stocktake - Hackman, O. Kwame; Gandji, Kisito; Ouedraogo, Ramata; Akoba, Leonard; Segnon, Alcade Christel; Salack, Seyni; Zougmore, Robert Bellarmin (2025)
The Paris Agreement mandates Parties to regularly enhance their Nationally Determined Contributions (NDCs), ensuring that their climate commitments remain ambitious, transparent, and progressively improved. The West Africa Regional Hub of the Independent Global Stocktake (iGST WA Hub) brings together over 500 non-state actors of the 15 West Africa countries, to complement countries in enhancing their contributions toward achieving the goals of the Paris Agreement. As part of a young fellowship program targeting civil society organizations (CSOs) within iGST WA Hub, a youth-led regional assessment of West African countries’ NDCs (including AICCRA countries) has been conducted. The youth-led regional assessment reveals that, while several issues remain outstanding, West African Parties have made notable efforts to enhance their climate ambitions, including setting more ambitious targets and allocating 30% of domestic resources as overall unconditional commitments. The climate commitments of West African countries, however, do not meet the expectations of the first Global Stocktake (GST) outcome for strengthening adaptation action, such as national inventories of climate impacts over time which were not explicitly addressed in most NDCs. AICCRA supported a regional validation workshop in which participants, including UNFCCC and NDC Partnership focal points from 14 West African countries, strongly recommended that the findings serve as evidence to inform for both national and regional policy processes, particularly in the development and implementation processes of NDCs 3.0. AICCRA could contribute to bridge the climate finance gap identified by leveraging its research and partnerships to package its validated, on-the-ground innovations as bankable projects, thereby attracting investment for West African countries’ conditional commitments and facilitating the technology transfer needed for transformative climate action.